Observation of effects of inter-atomic interaction on Autler–Townes splitting in cold Rydberg atoms - Silpa Baburaj Sheela; Shovan Kanti Barik; Varna Shenoy; Soham Chandak; Rejish Nath; Sanjukta Roy (New Journal of Physics)
We demonstrate the effect of inter-atomic interaction in highly excited Rydberg atoms via Autler–Townes (AT) splitting in cold atoms. We measure the AT splitting of the $\{5S_{1/2}, F = 2\} → \{5P_{3/2}, F^{^{′}} = 3\}$ transition of ^87 Rb atoms arising due to the strong coupling of the transition via the cooling beams used for the magneto-optical trap (MOT). The AT splitting is probed using a weakly coupled transition from $\{5P_{3/2}, F^{^{′}} = 3\}$ state to highly excited Rydberg states for a wide range of principal quantum numbers $(n = 35-117)$ . We observe the AT splitting via trap-loss spectroscopy in the MOT by scanning the probe frequency. We observe a drastic increase in the broadening of the AT splitting signal as a result of interaction-induced dephasing effect in cold Rydberg atoms for highly excited Rydberg states with principal quantum number n $\gt$ 100. We explain our observations using theoretical modeling and numerical simulations based on the Lindblad Master equation. We find a good agreement of the results of the numerical simulation with the experimental measurements.